2008
DOI: 10.2320/matertrans.ma200808
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Ductility and Hydrogen Permeability of Nb-Ti-Zr-Ni Alloys

Abstract: A series of Nb 40 Ti x Zr 12 Ni 48Àx alloys with different Ti/Ni ratios were prepared by arc melting in a purified argon atmosphere. The Ti/Ni ratio affected microstructures, crystal structures, ductility and hydrogen permeability (È) of these alloys. The values of hydrogen permeability È for the Nb 40 Ti x Zr 12 Ni 48Àx alloys increased with increasing temperature and were higher than those of pure Pd above 573 K. Hydrogen permeability at 673 K, i.e., È 673K and the volume fraction of the primary phase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Therefore, it is desirable to develop a new low-cost membrane by minimum addition or absence of Pd with high hydrogen permeability (Φ), ductility and resistance to the hydrogen embrittlement. In recent years, researchers have investigated the V-based [3][4][5], Nb-Ti-Ni (or Co) [6,7] and some amorphous alloy membranes [8][9][10] and resistance to the hydrogen embrittlement [11]. However, hydrogen permeation could not be measured due to the hydrogen embrittlement if the thickness of this alloy membrane is lower than 0.3 mm.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is desirable to develop a new low-cost membrane by minimum addition or absence of Pd with high hydrogen permeability (Φ), ductility and resistance to the hydrogen embrittlement. In recent years, researchers have investigated the V-based [3][4][5], Nb-Ti-Ni (or Co) [6,7] and some amorphous alloy membranes [8][9][10] and resistance to the hydrogen embrittlement [11]. However, hydrogen permeation could not be measured due to the hydrogen embrittlement if the thickness of this alloy membrane is lower than 0.3 mm.…”
Section: Introductionmentioning
confidence: 98%
“…There are two possible methods to solve the hydrogen embrittlement of this alloy. One is to reduce the content of Zr so as to reduce Φ and to enhance ductility [11]. The other is to add a small amount of other elements.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits strong HE resistance in a much larger hydrogen pressure range than that for Nb-based solid solution alloys. However, the hydrogen permeability of Nb 40 Ti 30 Ni 30 is not quite satisfactory for the practical applications 48 . In this work, the substitution of Nb by Mo in Nb 40 Ti 30 Ni 30 was investigated with respect to microstructural features and hydrogen dissolution, diffusion and permeation.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that appropriate substitution of Ti by Zr can induce a much higher hydrogen permeability (because of the higher hydrogen affinity of Zr than that of Ti) and comparable other properties [32,33]. Nevertheless, excessive addition of Zr leads to low ductility and serious hydrogen embrittlement due to the microstructural change and the inappropriately high hydrogen solubility [34]. Therefore, much of current research focuses on compositional modifications in these alloys to tailor the microstructures and hydrogen solubility and diffusivity for improved performance.…”
Section: Introductionmentioning
confidence: 94%
“…mechanically sealed with copper gaskets, these alloys must have at least some ductility. Most simply, a material that can be broken easily by hammering is qualitatively defined as brittle [32][33][34], while non-broken materials are defined as ductile.…”
Section: Ductilitymentioning
confidence: 99%